2021
DOI: 10.1021/acs.molpharmaceut.0c00574
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of P-Glycoprotein in the Gastrointestinal Tract of Humans and Rodents: Methodology, Gut Region, Sex, and Species Matter

Abstract: Intestinal efflux transporters affect the gastrointestinal processing of many drugs but further data on their intestinal expression levels are required. Relative mRNA expression and relative and absolute protein expression data of transporters are commonly measured by real-time polymerase chain reaction (RT-PCR), Western blot and mass spectrometry-based targeted proteomics techniques. All of these methods, however, have their own strengths and limitations, and therefore, validation for optimized quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 53 publications
6
30
0
Order By: Relevance
“…The normal meal caused an increase from the fasted state for males (+50%), but not for females, where jejunal MRP2 expression was 4.23 ± 0.57 and 4.28 ± 0.72 ng/mg for the fasted and normal meal interventions, respectively. The fasted and housing food (normal meal) P-gp-related findings were similar to previous findings in our research group by Dou et al using a validated LC-MS/MS method [19], a Western blot method [20] and PCR [16]. Importantly, the inter-individual variations were low in this study, shown by narrow standard deviation in the Supplementary Materials, Tables S1-S3, in comparison to the Western blotting and LC-MS/MS methods [16,19,20].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The normal meal caused an increase from the fasted state for males (+50%), but not for females, where jejunal MRP2 expression was 4.23 ± 0.57 and 4.28 ± 0.72 ng/mg for the fasted and normal meal interventions, respectively. The fasted and housing food (normal meal) P-gp-related findings were similar to previous findings in our research group by Dou et al using a validated LC-MS/MS method [19], a Western blot method [20] and PCR [16]. Importantly, the inter-individual variations were low in this study, shown by narrow standard deviation in the Supplementary Materials, Tables S1-S3, in comparison to the Western blotting and LC-MS/MS methods [16,19,20].…”
Section: Discussionsupporting
confidence: 89%
“…The fasted and housing food (normal meal) P-gp-related findings were similar to previous findings in our research group by Dou et al using a validated LC-MS/MS method [19], a Western blot method [20] and PCR [16]. Importantly, the inter-individual variations were low in this study, shown by narrow standard deviation in the Supplementary Materials, Tables S1-S3, in comparison to the Western blotting and LC-MS/MS methods [16,19,20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…MDR1 recognizes a wide range of lipophilic substrates. In the gastrointestinal mucosa, MDR1 drains substrates to the luminal side, and in cerebrovascular endothelial cells, MDR1 regulates the substrate distribution into the brain tissue [ 6 , 7 , 8 , 9 ]. ABCB4 (MDR3) acts as a flippase for phosphatidylcholine, a phospholipid that forms cell membranes, and changes the composition of the phospholipids that are present in the cell membranes.…”
Section: Physiological Functions Of Drug Transportersmentioning
confidence: 99%
“…The poor oral bioavailability of progesterone has primarily been attributed to extensive metabolism in the liver [ 7 ]. However, in the current literature, very little information exists on progesterone intestinal metabolism, although extensive enzymatic expression is found throughout the small intestinal mucosa [ 8 , 9 , 10 , 11 , 12 ]. Furthermore, the small intestine contains appreciable levels of bacteria [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%